The Effectiveness of the TPR (Total Physical Response) Method in Enhancing Students' Vocabulary - Catur Sugiarti Putri; Taslim; Syarifuddin (International Journal of Integrative Sciences, 2025)
Introducing English vocabulary to young learners is essential for building a strong language foundation, as it enhances their reading, writing, listening, and speaking skills. However, research indicates that elementary students often face significant challenges in vocabulary acquisition, emphasizing the need for innovative teaching strategies that go beyond traditional methods. One effective approach for teaching English vocabulary to EFL (English as a Foreign Language) beginners is the Total Physical Response (TPR) method. This study aimed to evaluate the effectiveness of the TPR method in improving students' vocabulary skills. Using a pre-experimental design with a one-group pretest-posttest framework, the research focused on fourth-grade students at SD Inpres 7/83 Pasempe. Data analysis, conducted through a paired sample t-test, revealed a significant increase in average scores from the pre-test to the post-test. The substantial improvement in scores highlights the effectiveness of the TPR method in helping young learners understand and retain new vocabulary. This approach leverages the intrinsic connection between physical activity and cognitive processes, making the learning experience more engaging and lasting